Patterns of corporate governance : creating successful organizations by the board - Egwuonwu, Roland; Muttallab, Umaru (Lagos, Nigeria: Stride Associates, 2000)
The book harps on the indispensability of responsible governance in the pursuit of sustained national and industrial excellence. the need for a sound culture of governance which is consistent with the rate of change in the global corporate village is underscored by the book.
Published in honour of Alhaji (Dr.) Umaru A. Muttalab, for his eminent contributions to corporate governance.
Includes bibliographical references and index.
oif 11/07/2018
Loans
Keywords: Corporate governance; Executive management